Electrochemical properties of anthracene-based lithium-solvated electron solutions - Liu, Zhihao (2020)
The conductivity and open-circuit voltage (OCV) of lithium-solvated electron solutions (LiSESs) based on anthracene in tetrahydrofuran were studied by both experimental measurements and density functional theory calculations with a range-separated functional based on the M06 form and the Solvation Model based on Density (SMD). The OCV was found to decrease with increasing temperature and the ratio of lithium to anthracene. The enthalpy change (ΔH) of LiSESs was the internal energy change of the cell reaction. The conductivity of LiSESs exhibited a weakly metallic-like behavior. The electron transport was facilitated by molecular collisions promoted by the formation of dimeric structures as intermediates. The conductivity of LiSESs at 295.15 K presents positive correlation with the entropy change (ΔS) associated with the variation in the ratio of lithium to poly-aromatic hydrocarbon, including p-terphenyl, anthracene, and triphenylene.